Formalizing voting protocol in process algebra - Ban, Ainita; Shukur, Zarina (Praise Worthy Prize, 2014)
Electronic voting can be seen as one of the best alternatives of today’s election for it will provide many advantages such as efficient and accurate data management and accumulation as well as convenience to voters. In order to gain confidence and trust among people to implement electronic voting system, a formal method is chosen. Formal method has been proven successfully in verifying properties. This paper presents work of specifying voting protocol formally using CSP (Communicating Sequential Process). We demonstrated the work on two voting. The first protocol was using blind signature based while the second was blind signature and threshold IBE (Identity Based Encryption) scheme. The specification will be used in verifying properties of voting protocol in later work.